استخدام معطيات التحسس النائي لرصد التغيرات البيئيه لاهوار جنوب العراق - النائلي علي (University of Thi-Qar Journal of Science, 2010)
This study has dealt with assessing reality of marshland through monitoring the changes that took place from 1999-1972 and for a zone falling between(32-30) northern and (49-46)eastern which has constituted an area of 2098 km2 through preparing thematic maps and by depending on three false colored satellite image namely , landsat and resurs satellite taken in 1972-1990-1999 . After interpreting the satellite data of preparing these maps for the land use and land cover depending on the USGS system initiated by Anderson 1976, it has been found out that marshland is undergoing a constant deterioration as a result of the decrease of its area as a result of the process of drying practiced by the former regain by then.The area of marshland has been reduced 563.55km2 in 1972 to 315.01km2 in 1990 until it became 113.43 km2 in 1999, the area of dried lands from zone in 1972 to 69.36 km2 in 1990 moving upwards to reach 239.87 in 1999 therefore this has lead to the increase of dried land which includes arid land the natural-dried salty arid land and the man wade arid dried land from 1267.26km2 in 1972 to 1287.1km2 in 1990 and to1294.54km2 in 1999.The study points to the clear deterioration the marsh land are undergoing in southern Iraq which has been wade clear by the findings of study which has covered a considerable part of marsh land in southern Iraq